Specificity of Conveying Female Character Through Lexical-Phraseological Expressions in Kazakh and English Language Works of Fiction (Eurasian Journal of Philology Science and Education, 2025)
Currently, active research on gender phraseological expressions and the cognitive aspect of the concept of "woman" is being conducted in cognitive linguistics and linguocultural studies, leading to convincing conclusions. Therefore, studying the specificity of transmitting female behavior through lexico-phraseological expressions is an urgent issue. The purpose of this research is to identify lexical-phraseological expressions characterizing female behavior in Kazakh and English fiction, analyze their ethno-cultural differences, and illustrate them with concrete examples. When examining the frequency and structure of these expressions, the formulation of their essential value in dictionaries was considered. The selection of these expressions, using descriptive and comparative analysis and linguistic observation, forms the scientific foundation of this study. Their usage in fiction, along with the issue of their practical relevance today, determines the scientific and practical significance of this work.This research draws on Kazakh and English literary works to analyze how female behavior is conveyed through phraseological expressions and how they align with national culture, worldview. The study demonstrates that these expressions vary depending on the time and place of writing, the author's language, and each nation's indigenous culture. Lexical and comparative analytical approaches are applied to explore these variations.Through the selection and study of bilingual literary works, a set of phraseological expressions reflecting female behavior in Kazakh and English has been compiled, revealing their essence. Identifying and modernizing phraseological expressions related to femininity, whether obsolete or found only in artistic works, and comparing them with English equivalents contributes significantly to linguistics. The search and selection of such expressions in literary works, along with defining their usage within national mentality, constitute the practical core of this research. Its comparative analysis with linguistic samples from other languages, exploration of linguistic richness, and revival of obsolete phraseological expressions underscore the broader value, ultimate goal of linguistic studies.Keywords: Kazakh and English language, female character, lexical-phraseological expressions, linguoculturology, artistic work.